2012
DOI: 10.2174/138955712798868940
|View full text |Cite
|
Sign up to set email alerts
|

CDC25 Phosphatase Inhibitors: An Update

Abstract: The cell division cycle 25 (CDC25) family of proteins is a group of highly conserved dual-specificity phosphatases. They are key regulators of normal cell division and the cell response to DNA damage, and play a fundamental role in transitions between cell cycle phases during normal cell division, via the activation of CdK/cyclin complexes. Their abnormal expression, detected in a number of tumors, often correlated with a poor clinical prognosis, implies that their dysregulation is involved in malignant transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 69 publications
2
65
0
Order By: Relevance
“…Cyclin A binds and activates CDK2, and thus promotes both cell cycle G1/S and G2/M transitions (Lim and Kaldis, 2013). In addition, Cdc25 phosphatases are also central targets and regulators of the G2/M checkpoint mechanisms (Lavecchia et al, 2012). The present results showed that protein expression of cyclin A and Cdc25A were down-regulated after the treatment of luteolin, supporting the arrest of cell cycle progression at the G2/M phase.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Cyclin A binds and activates CDK2, and thus promotes both cell cycle G1/S and G2/M transitions (Lim and Kaldis, 2013). In addition, Cdc25 phosphatases are also central targets and regulators of the G2/M checkpoint mechanisms (Lavecchia et al, 2012). The present results showed that protein expression of cyclin A and Cdc25A were down-regulated after the treatment of luteolin, supporting the arrest of cell cycle progression at the G2/M phase.…”
Section: Discussionsupporting
confidence: 61%
“…The pathway, therefore, is gaining attention as a molecular target for CCA treatment strategies.governed by the cell cycle, which is an order of events that is tightly regulated by a number of serine/threonine protein kinases known as cyclin-dependent kinase (CDK) and cyclins (Lim and Kaldis, 2013). In addition, the cell division cycle 25 (Cdc25) phosphatases are also a family of proteins that are vital to cell cycle regulation (Lavecchia et al, 2012). Furthermore, cancer cells acquire alternations for enhanced survival and become apoptosis-resistant to anticancer therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Cdc25 inhibitors have been pursued as promising chemotherapeutic agents that could block cell-cycle progression in cancerous cells, but these compounds have had only limited clinical success (Lavecchia et al 2012 Figure S3. Purified phosphatases.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the group of genes expressed Ag independently by OT1 but not AND T cells include cell cycle-associated Cdc25b, Cdc26, Cdc34, and Cdc37. Both Cdc25 and Cdc34 are regulators of proliferation for which specific inhibitors have identified that block cell cycle progression of tumor cells (57,58). Tbx21 encoding T-bet, the transcription factor regulating CTL differentiation, also falls into this category (Fig.…”
Section: Gene Expression Following Transient and Persistent Stimulationmentioning
confidence: 99%